KUAT TEKAN BETON AWAL TINGGI DENGAN VARIASI PENAMBAHAN SUPERPLASTICIZER DAN SILICA FUME - Hakas Prayuda; Fadillawaty Saleh (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2019)
Concrete is one of the construction materials of combination between cement, fine aggregate, coarse aggregate, and water mixed into one solid mass. The work of concrete making can be added a mineral additive as well as chemical additive (admixture) for the interest in construction work. In some cases construction work is desirable for concrete to produce optimum strength during the early age of the concrete so that the timing of concreting work can be shortened. The strength of concrete at the early age can be increased with added mineral (additive) and chemical (admixture) materials. This research made a mixture of concrete with 7 variations of mixture with total specimen 54 sample of cylindrical size with diameter 15 cm and height 30 cm. Tests conducted in the form of testing workability and compressive strength of concrete at the age of 3 days, 7 days and 28 days. Through this study obtained the right composition to make concrete with a high early age of compressive strength.